Girls, and gender and power relationships in an urban middle school. Issue 4 (7th June 2017) - McCullough, Susan
ABSTRACT: This paper describes the practices employed by middle school girls in New York City to negotiate their postfeminist school environment and considers the contested notion of girls' agency. Based on an exploratory ethnographic study, the data reveal that girls – to varying degrees of success – enacted a range of practices to gain power over the pervasive sexism as well as the masculine hegemonic behavior that was the norm at their school.